Finite Element Analysis of Disbondment in Thermoplastics Composite Pipe (TCP) Fitness for Surface (FFS) - AZIZI, MUHAMMAD FAKHRU RAZI (IRC, 2020)
In this work, we study the stress distribution analysis and thermal distributin analysis on TCP composite with failure mode which is cathodic disbondment using finite element model from ANSYS Workbench Software. Mesh sensitivity study in this model has concluded to 12 number of mesh until it produces insignificant difference in stress value as the number of mesh is more sensitive. Mesh sensitivity analysis can be performed by simulating models with different number of mesh and element sizes under the condition applied on the model. The variation of the meshes are done to get accepted level tolerance that can be found out from grid independence test. This is done by varying the mesh size from coarse to fine and checking the output result for each mesh.